2018
DOI: 10.1097/md.0000000000010974
|View full text |Cite
|
Sign up to set email alerts
|

Rare ocular manifestations in an 11-year-old girl with incomplete Kawasaki disease

Abstract: To the best of our knowledge, this is the first documented case of incomplete Kawasaki disease with severe posterior segment lesions. The local use of dexamethasone in the eye was effective in our patient. Surgical intervention might not be necessary even though the initial symptoms could be devastating. The eye should be monitoring the eye routinely in patients with Kawasaki disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Our fourth patient fulfilled both KD and MIS-C criteria and presented with several clinical characteristics of both diseases. Since no cardiac or coronary involvement, that could help in the differential diagnosis, was identified, a definite diagnosis was not possible [ 19 ]. Therefore, the patient was treated with IVIG, glucocorticoids, and aspirin, covering both KD and MIS-C possible diagnoses, and responded well to the therapy without any long-term sequelae (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our fourth patient fulfilled both KD and MIS-C criteria and presented with several clinical characteristics of both diseases. Since no cardiac or coronary involvement, that could help in the differential diagnosis, was identified, a definite diagnosis was not possible [ 19 ]. Therefore, the patient was treated with IVIG, glucocorticoids, and aspirin, covering both KD and MIS-C possible diagnoses, and responded well to the therapy without any long-term sequelae (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al in 2018 reported a case of a girl with incomplete KD and reduced eye volume, cataracts, retinal detachment, choroid, and chorioretinal folds. Besides IVIG, she was treated with eye steroids and had total recovery within one month [ 7 ]. More recently, Suganuma et al described a seven-year-old boy who developed retinal vasculitis with impairment of visual acuity, and also refer to the only three reports in the literature with long-term visual impairment due to KD [ 8 ].…”
Section: Discussionmentioning
confidence: 99%